Short-term effect of household indebtedness and risk of alcohol use disorder among Korean youth: 2017–2020 longitudinal panel study - Kim, Jinhyun; Yun, Il; Kim, Hyunkyu; Park, Eun-Cheol (Frontiers in Psychiatry, 2023)
Background: In Korea, household debt has increased recently among young adults, especially during the COVID-19 pandemic. Household debt may potentially lead to numerous outcomes including alcohol use disorder (AUD). The aim of this study was to investigate the relationship between a change in indebtedness and the risk of developing AUD. Methods: A total of 5,091 participants (2,720 men and 2,371 women) were included during a fouryear study period. Indebtedness was divided into four groups: no debt a year ago and at present (group 1), paying off a year's debt (group 2), newly incurred current debt after a year when there was no debt (group 3), and indebtedness a year ago and at present (group 4). Groups 2, 3, and 4 were also divided into subgroups based on debt characteristics. AUD risk was evaluated by the CAGE scale, and a score of 2 or higher was defined as AUD high risk. Several time-varying socioeconomic and health-related characteristics were adjusted. Results: Participants who indicated indebtedness at present (groups 3 and 4) were more likely to be AUD high-risk compared to group 1 in both genders (men: adjusted relative risk [aRR] = 1.031, 95% CI [1.014-1.049] in group 3, aRR = 1.028, 95% CI [1.007-1.050] in group 4; women: aRR = 1.039, 95% ] in group 3, aRR = 1.028, 95% CI [1.007-1.050] in group 4). Even paid-off debt affected the risk of AUD among female participants (aRR = 1.018, 95% CI [1.001-1.034] in group 2). Women whose amount of debt increased for one year were more likely to be AUD highrisk compared to group 1. Women showed higher aRR than men for increasing CAGE scores by one unit in all debt subgroups. Conclusions: Our research demonstrated a possible link between indebtedness and a heightened risk of AUD. These results underscore the importance of implementing targeted screening and interventions for AUD, particularly among young women who are facing mounting levels of debt.